Efficacy of Thymol on the Scolices of Hydatid Cyst - Farnaz Kheirandish; Abdolrazagh Marzban; Leila Masoori; Morteza Nourmohammadi; Kobra Moradpour; Kourosh Cheraghipour * (Lorestan University of Medical Sciences, 2020)
As one of the major constituents of medicinal plant extracts, thymol has remarkable anti-worm properties. The contents of 5 English databases, including Scopus, PubMed, Web of Science, Embase and Google Scholar in the time span from 2008 to December 2019 were searched. All the relevant studies with English abstracts were searched regardless of the language of their discussions. Words and terms are used as syntax with specific tags from each database. Eleven out of 2146 studies were found eligible for evaluation. The findings indicated that 100% of the studies were about hydatid cysts and thymol. Moreover, 6 in vitro (55%) and 3 in vivo studies (27%), as well as 2 studies both in vitro and in vivo (18%), were carried out. According to these studies, thymol, as one of the major constituents of plant compounds, has a significant role in killing and reducing the parasitic protoscolex in vitro and in vitro. Likewise, thymol could have significant effects on restructuring protoscoleces and ultimately on their mortality. Thymol has an anti-hydatid cyst effect with the least side effects, and could be a good alternative to the treatment and prevention of anti-protoscoleces infections or in other studies against other helminth infections.